Temperature dependence of the anharmonic decay of optical phonons in carbon nanotubes and graphite - Chatzakis, Ioannis; Yan, Hugen; Song, Daohua; Berciaud, Stéphane; Heinz, Tony F. (My University, 2011)
We report on the temperature dependence of the anharmonic decay rate of zone-center (G mode) optical phonons in both single-walled carbon nanotubes and graphite. The measurements are performed using a pump-probe Raman scattering scheme with femtosecond laser pulses. For nanotubes, measured over a temperature range of 6 K–700 K, we observe little temperature dependence of the decay rate below room temperature. Above 300 K, the decay rate increases from 0.8 to 1.7 ps−1. The decay rates observed for graphite range from 0.5 to 0.8 ps−1 for temperatures from 300 K–700 K. We compare the behavior observed in carbon nanotubes and graphite and discuss the implications of our results for the mechanism of the anharmonic decay of optical phonons in both systems.